Safety and Efficacy of Mavrilimumab For Rheumatoid Arthritis: A Systematic Review and Meta-Analysis - Shamseldin, Laila S.; Shawqi, Mohamed Mohamed; Al Hashem, Noor Adel; Alhyari, Majd A. H.; Abd Elazeem, Hossam Aldein Samir; Elghazaly, Shrouk M.; Hamdallah, Aboalmagd; Ragab, Khaled Mohamed; Nourelden, Anas Zakarya (Current Rheumatology Reviews, 2021)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by progressive swelling and stiffness in the joints. Mavrilimumab is a human monoclonal antibody that may block the autoimmune mechanism of the antibodies causing RA. Objective: We aim to assess the safety and efficacy of Mavrilimumab in treating rheumatoid arthritis. Methods: We conducted an online search using PubMed, Scopus, Web of Science, and Cochrane CENTRAL till June 2019, and updated the search in May 2020, using relevant keywords. We screened studies for eligibility. Data were extracted from eligible studies and pooled as Risk ratio (RR) with a 95% confidence interval (CI), using Review Manager software (ver.3.5). Results: Five studies (with 1145 patients) were eligible to our criteria. Pooled result from three trials showed a significant reduction in Disease Activity Score 28 based on C-reactive protein (DAS28-CRP) remission < 2.6 after 12 weeks (RR = 3.31, 95% CI [1.53, 7.18], P = 0.002), American College of Rheumatology (ACR) 20, after 12 weeks (RR = 2.38, 95% CI [1.80, 3.16], P < 0.00001), ACR 50, after 12 weeks (RR = 2.93, 95% CI [1.67, 5.15], P = 0.0002), ACR 70, after 12 weeks (RR = 4.90, 95% CI [1.60, 15.00], P = 0.005). Mavrilimumab not associated with a significant adverse event (RR = 1.22, 95% CI [0.89, 1.68], P = 0.22). Conclusion: We found that subcutaneous Mavrilimumab was effective and well-tolerating in treating RA patients, with no significant adverse events.
Keywords: monoclonal antibody